ROLES AND FUNCTION OF MAANYANESE DAYAK’S BALIAN SONGS IN 4.0 INDUSTRIAL ERA - Rusma Noortyani; Maryaeni Maryaeni (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
This research is based on the urgent need to safeguard the continuation of local cultureswhen faced to any foreign culture’s existence which can easily turn invasive in the midst of 4.0 industrial era and modernization. The balian songs have their own roles and functions that can be recorded as digital-archieve as one of concrete ways to safeguard local cultures in this 4.0 industrial era. The balian welcoming song is sung as both the expression of joy and honor to all the guests attending and walking down the aisle to the bridegrooms. Its common functions are, among others: 1) opening the wedding ceremony while parading the groom to the bride’s house; 2) guarding or protecting the groom from various potential misfortunes and or dangers coming from outsider parties; and 3) showing that the groom belongs to higher, or mid to upper, social and economic classes. The balian song of advice is sung to accompany the groom walking down the aisle. The role is to help the groom steeling his heart and thus readying him to make any lovesake’s sacrifice for his future wife. The advice song functions, among other: 1) to open the pantun (local couplets equivalent to those of traditional English) to intentionally put off the upcoming groom, for such delay is deemed necessary to show the couple’s readiness to make common sacrifice in their later household and 2) to better prepare the future husband’s perseverance to overcome any oncoming difficulties. Thus, the digital recording and archieving of balian songs require both the government and society’s utmost cares and immediate acts as that digitalization of cultural assets can help protecting various Maanyanese Dayak’s cultural heritage, especially the balian songs, to all future generations.